Analisis Kecenderungan Kemampuan Pengambilan Keputusan Perempuan Jawa Terhadap Persoalan Kehidupan - Muya Barida (MUWAZAH : jurnal kajian gender, 2017)
Each individual is faced with the problem of life which demands an ability to make decisions. Decision-making ability of the individual to one another is not the same. This difference is due to the factors that influence decision-making, both internal factors, and external factors. The analysis of the tendency of decision-making ability of Javanese women is very interesting to do. The purpose of analysis in order to obtain a clear picture of the tendency of Javanese women in decision-making on issues that it faces life every day. In general, people use the four processes of different decision-making ability, the strategy of independent decision making, logical, hesitated, and impulsive. The results obtained by analysis of Java that women tend to make decisions carefully, do not rush, take more time to think, and need others to seek reinforcement. This is due to the belief of Javanese women, the decision may affect the lives of themselves and others. Therefore, the decision-making process is emphasized. The process through which relies on decision-making style. Javanese women tend to have a logical decision-making strategy.